Improving Reliability of Wireless Sensor Network (WSN) Using Network Coding Multipath Routing - Abdurohman, Maman (ComTech: Computer, Mathematics and Engineering Applications, 2017)
This research proposed new method to improve performance of WSN. It used network coding on transmission scheme. The researcher had modified the existing network coding multipath routing for a novel node selection to own residual power node in network coding routing mechanism and to improve reliability of a WSN. This routing mechanism was placed in router for routing purpose. Then, Software network simulation method was done by using OMNET++ platform and MiXiM Framework library. The result shows that proposed method to select nodes and execute network coding succeeds on improving performance of WSN like the reliability compared to the previous method.